Deficiently Default‐Worthy Diffusions. Issue 72 (July 2014) - Osband, Kent
Abstract Modeling credit quality as diffusion is easy. Working out the market pricing implications is straightforward. Getting the straightforward implications of easy models to even roughly reflect observed pricing is hard.